A Multicentre, Randomised, Double Blind, Parallel Design, Placebo Controlled Study to Evaluate the Efficacy and Safety of Uthever (NMN Supplement), an Orally Administered Supplementation in Middle Aged and Older Adults - Huang, Hao (Frontiers in Aging, 2022)
Objective: The purpose of the study was to evaluate the anti-ageing effect of NMN and its safety in a double-blind, parallel, randomized controlled clinical trial. Methods: The study was carried out in 66 healthy subjects between ages 40 to 65 years, instructed to take two capsules (each containing 150 mg. NMN or starch powder) once a day after breakfast for 60 days daily. Results: At day 30 NAD+/NADH levels in the serum showed noteworthy increase i.e. by 11.3% whereas the placebo group had shown no change at all. At end of study i.e. day 60 the NAD+/NADH levels were increased further by 38% compared to baseline against mere 14.3% in the placebo group. In case of SF 36, at day 60 the Uthever group showed a rise of 6.5% whereas the placebo group was merely raised by 3.4%. At the end of the study, mean HOMA IR Index showed a rise of 0.6% among Uthever group and 30.6% among Placebo group from baseline. Conclusion: The rise in the levels of NAD+/NADH at Day 30 and Day 60 illustrated the potential of Uthever to raise the levels of NAD+ in the cells, which is linked to higher energy levels and anti-aging effect. Increased sensitivity to insulin has also been linked to anti-aging. There was no noteworthy change in HOMA score in the Uthever group whereas there was a noteworthy rise in the placebo group, demonstrating the anti-aging effect of Uthever as in its absence the parameter worsened.